Some Improved Estimators in Double Sampling Using two Auxiliary Variables - Mohammad S. Ahmed (Sultan Qaboos University Journal for Science, 2015)
Dash and Mishra [1] suggested an improved class of estimators without defining the optimum estimator. However, they gave the wrong Taylor’s series expression of their class of estimator and their minimum mean squared error expressions are also incorrect. Here we show that Ahmed et al.’s [2] class of chain estimators is more efficient than Dash and Mishra’s [1], with minimum mean squared error.